Analisis Produktivitas Data Center dengan Menggunakan Metode Objective Matrix dan Analytical Network Process di Dinas Kominfo Kaltim - Fikri Saifullah Rahman; Utomo, Dutho Suh; Tosungku, La Ode Ahmad Safar (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Measurement of productivity in the Diskominfo Kaltim data center is crucial for several reasons. One of these reasons is the significant energy consumption associated with data centers. Furthermore, there has been no prior measurement of productivity in the Diskominfo Kaltim data center. In efforts to measure and analyze data center productivity, the Objective Matrix (OMAX) method can assist in identifying factors influencing productivity improvement. Besides utilizing the OMAX method for productivity measurement, the Analytical Network Process (ANP) method is employed for weighting. ANP can accommodate the interdependencies among criteria and sub-criteria. In August 2023, a performance indicator of -47.48% was obtained, indicating a decrease in productivity by 47.48% compared to the standard performance. In September 2023, the performance indicator was 23.342%, signifying an increase in productivity by 23.342% compared to the standard performance. In October 2023, the performance indicator was 127.809%, indicating a significant increase in productivity by 127.809% compared to the standard performance. Keywords: Analytical Network Process, Objective Matrix, Productivity